Loneliness Progression Among Older Adults During the Early Phase of the COVID-19 Pandemic in the United States and Canada. (14th December 2021) - Lin, Tian; Horta, Marilyn; Heald, Kristen; Heemskerk, Amber; Darboh, Bri; Levi, Adina; Spreng, R Nathan; Turner, Gary R; Ebner, Natalie C
Abstract: Objectives: Older adults are at high risk for complications from coronavirus disease 2019 (COVID-19). Health guidelines recommend limiting physical contact during the pandemic, drastically reducing opportunities for in-person social exchange. Older adults are also susceptible to negative consequences from loneliness, and the COVID-19 pandemic has likely exacerbated this age-related vulnerability. Methods: In 107 community-dwelling older individuals (65–90 years, 70.5% female) from Florida, the United States, and Ontario, Canada, we examined change in loneliness over the course of the pandemic after implementation of COVID-19-related physical distancing guidelines (March–September 2020; T1–T5; biweekly concurrent self-report) using multilevel modeling. We also explored gender differences in loneliness during the early phase of the COVID-19 pandemic at both data collection sites. Results: Consistent across the 2 sites, levels of loneliness remained stable over time for the full sample (T1–T5). However, our exploratory moderation analysis suggested gender differences in the trajectory of loneliness between the United States and Canada, in that older men in Florida and older women in Ontario reported an increase in loneliness over time. Discussion: Leveraging a longitudinal, binational data set collected during the early phase of the COVID-19 pandemic, this study advances understanding of stability and change in loneliness among a North American sample of individuals aged 65 and older faced with the unique challenges of social isolation. These results can inform public health policy in anticipation of future pandemics and highlight the need for targeted intervention to address acute loneliness among older populations.